Impact of globalization on livelihood of women in Tamilnadu - Gandhimathi, A. (Tamil Nadu: Women MAPOVI-TN, 2004)
"A study by Women Movement Against Poverty and Violence - Tamil Nadu ; researcher : A. Gandhimathi"